Penchinones A–D, two pairs of cis-trans isomers with rearranged neolignane carbon skeletons from Penthorum chinense1. Issue 94 (14th October 2015) - He, Ya-Cong; Peng, Cheng; Xie, Xiao-Fang; Chen, Ming-Hua; Li, Xiao-Nian; Li, Meng-Ting; Zhou, Qin-Mei; Guo, Li; Xiong, Liang
<x xml:space="preserve">Abstract</x> Two pairs of cis-trans isomers with new rearranged neolignane carbon skeletons from Penthorum chinense.